Abstracts of Philippine researches in guidance 1971-1976 - Agustin, Leila M.; Hidalgo, Namnama P.; Munarriz, Natividad (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1977)
This special problem aims to provide guidance workers and researchers with a listing of abstract of researches on guidance done from 1971 to 1976. It continues "Ten Years of Philippine Researches in Guidance, 1961-1970" by the Philippine Guidance and Personnel Association (PGPA) and "Abstracts of Philippine Researches in Guidance, 1951-1960" by Estella Antonio. Bibliographical catalogs and lists of various libraries in Metro Manila were utilized in compiling and locating theses and dissertations. Periodical indexes were used for gathering titles of researches published in local journals. In addition, card catalogs of different libraries were also consulted. Reports on original researches were found in fifteen institutional libraries in Manila.
A total of three hundred three (303) researches were identified and listed. Of these, two hundred fifty (250) researches were located, analyzed and abstracted. The abstracted researches include two hundred twenty-two (222) masteral theses, sixteen (16) doctoral dissertations and twelve (12) researches published in local journals. Although fifty-three (53) of the researches identified were not located, these were nevertheless included in the bibliography.
The abstracts are arranged alphabetically under the author's surname. Each entry includes the abstract number, bibliographic data (author, title, degree earned, university or college and year completed, number of leaves or pages) and the abstract. Only the abstract number and the bibliographic data are given for researches which could not be located. The term "Not Available" is indicated in lieu of the abstract. A subject index is provided.
The bibliographic essay which serves as an introduction to the bibliography and abstract identifies reference literature in the field of guidance in the Philippines since 1951.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Personnel service in education -- Philippines -- Abstracts